Enterobius vermicularis Infestation with Acute Perforated Suppurative Appendicitis in a Child: Cause or Mere Association? - Chilkar, Sujeet M.; Leelakumar, Venkat; Musthyala, Naga Bharati (Journal of Pediatric Infectious Diseases, 2016)
Acute appendicitis is the commonest cause of surgical emergency, occurring worldwide and affecting all age groups. The pathology is most likely the obstruction of lumen of the appendix due to multifactorial etiology. Acute appendicitis due to helminths and protozoan infection is quite rare. The causal relationship of appendicitis and pinworms (Enterobius vermicularis or oxyuris) remains controversial. Here, we report a case of an 8-year old boy with pinworm discovered inadvertently after appendectomy in a highly inflamed perforated appendix.
Keywords: appendicitis; appendectomy; helminths; pinworm; Enterobius vermicularis